Impact of timing between insulin administration and meal consumption on glycemic fluctuation and outcomes in hospitalized patients with type 2 diabetes - Lim, Shu Fang (2021)
Background: The effect of time interval from insulin injection to meal consumption (“insulin-meal”) on glycemic fluctuation and outcomes is not well understood. Objective: This study aims to investigate the impact of coordinated versus mismatched insulin-meal administration on glycemic fluctuation and outcomes among hospitalized patients with type 2 diabetes (T2D).Methods: Hospitalized patients with T2D who received at least 1 dose of insulin as part of sliding scale regimen were included. Data such as capillary blood glucose values and insulin-meal time intervals were collected.Results: A total of 215 patients with 840 insulin-meal encounters were eligible for the study. Compared to the insulin-meal mismatch group (n = 206), the coordinated insulin-meal administration group (n = 9) had lower mean glycemic fluctuation (6.5 [2.6] mmol/L vs 5.6 [2.5] mmol/L or 117 [47] mg/dL vs 100 [45] mg/dL). Encounters with the insulin-meal time interval of 30 to 45 minutes (n = 172) were associated with the lowest percentage of severe hyperglycemia occurrences (13%) as compared to encounters with time interval of 0 to 29 minutes (n = 280, 15%) and more than 45 minutes (n = 246, 16%). Conclusion: Coordinated insulin-meal administration was associated with lower glycemic fluctuation among hospitalized patients with T2D.